Preserving Cultural Identity of Angklung Paglak through Visual Identity-based Approach - Zzyafra Iomaski Zihana; Inne Chaysalina (ITB Journal Publisher, DRPM ITB, 2023)
Angklung Paglak, a traditional musical instrument rooted in the rich cultural heritage of Kemiren Village, Banyuwangi, East Java, Indonesia, has played a pivotal role in entertaining farmers and expressing gratitude during the Great Harvest ceremonies. However, with the gradual decline of traditional harvest practices and the advent of modernization, the once vibrant Angklung Paglak tradition faces the risk of extinction. This study used the endogenous development theory to investigate the historical existence of Angklung Paglak and its evolution under the influence of tourism, emphasizing the structure of awareness, social relations, and practical techniques. In summary, by employing an ethnographic approach, the research involved real-world observations and interactions with local participants for one year to gain first-hand insight into the complex interplay between Angklung Paglak as a cultural asset and tourist attraction. The envisioned visual identity plays a significant role in fostering cultural continuity and unity, thus revitalizing and preserving Angklung Paglak’s significance within the community’s collective memory.